Association of Drug-Metabolizing Enzyme and Transporter Gene Polymorphisms and Lipid-Lowering Response to Statins in Thai Patients with Dyslipidemia - Vanwong N; Tipnoppanon S; Na Nakorn C; Srisawasdi P; Rodcharoen P; Medhasi S; Chariyavilaskul P; Siwamogsatham S; Vorasettakarnkij Y; Sukasem C (Dove Medical Press, 2022)
Natchaya Vanwong,1,2 Sayanit Tipnoppanon,1 Chalitpon Na Nakorn,3 Pornpen Srisawasdi,4 Punyanuch Rodcharoen,4 Sadeep Medhasi,5 Pajaree Chariyavilaskul,2,6,7 Sarawut Siwamogsatham,2,8,9 Yongkasem Vorasettakarnkij,2,9 Chonlaphat Sukasem10- 12 1Department of Clinical Chemistry, Faculty of Allied Health Sciences, Chulalongkorn University, Bangkok, Thailand; 2Cardiovascular Precision Medicine Research Group, Special Task Force of Activating Research (STAR), Chulalongkorn University, Bangkok, Thailand; 3Department of Clinical Pharmacy, Faculty of Pharmaceutical Sciences, Prince of Songkla University, Songkhla, Thailand; 4Division of Clinical Chemistry, Department of Pathology, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 5Department of Transfusion Medicine and Clinical Microbiology, Faculty of Allied Health Sciences, Chulalongkorn University, Bangkok, Thailand; 6Department of Pharmacology, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 7Clinical Pharmacokinetics and Pharmacogenomics Research Unit, Chulalongkorn University, Bangkok, Thailand; 8Chula Clinical Research Center, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 9Department of Medicine, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 10Division of Pharmacogenomics and Personalized Medicine, Department of Pathology, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 11Laboratory for Pharmacogenomics, Somdech Phra Debaratana Medical Center (SDMC), Ramathibodi Hospital, Bangkok, Thailand; 12Pharmacogenomics and Precision Medicine, The Preventive Genomics & Family Check-up Services Center, Bumrungrad International Hospital, Bangkok, ThailandCorrespondence: Chonlaphat Sukasem, Division of Pharmacogenetics and Personalized Medicine, Department of Pathology, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, 10400, Thailand, Tel +66-2-200-4331, Fax +66-2-200-4332, Email chonlaphat.suk@mahidol.ac.thPurpose: Statins are increasingly widely used in the primary and secondary prevention of cardiovascular disease. However, there is an inter-individual variation in statin response among patients. The study aims to determine the association between genetic variations in drug-metabolizing enzyme and transporter (DMET) genes and lipid-lowering response to a statin in Thai patients with hyperlipidemia.Patients and Methods: Seventy-nine patients who received statin at steady-state concentrations were recruited. Serum lipid profile was measured at baseline and repeated after 4-month on a statin regimen. The genotype profile of 1936 DMET markers was obtained using Affymetrix DMET Plus genotyping microarrays.Results: In this DMET microarray platform, five variants; SLCO1B3 (rs4149117, rs7311358, and rs2053098), QPRT (rs13331798), and SLC10A2 (rs188096) showed a suggestive association with LDL-cholesterol-lowering response. HDL-cholesterol-lowering responses were found to be related to CYP7A1 gene variant (rs12542233). Seven variants, SLCO1B3 (rs4149117, rs7311358, and rs2053098); SULT1E1 (rs3736599 and rs3822172); and ABCB11 (rs4148768 and rs3770603), were associated with the total cholesterol-lowering response. One variant of the ABCB4 gene (rs2109505) was significantly associated with triglyceride-lowering response.Conclusion: This pharmacogenomic study identifies new genetic variants of DMET genes that are associated with the lipid-lowering response to statins. Genetic polymorphisms in DMET genes may impact the pharmacokinetics and lipid-lowering response to statin. The validation studies confirmations are needed in future pharmacogenomic studies.Keywords: drug-metabolizing enzymes, drug transporters, gene polymorphisms, statin